The Role of Local Governments in Spatial and Building Regulations: A Review of State Administrative Law - Widayanti; Kusworini; Widiati Dwi Winarni (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Local governments are pivotal in spatial planning and building regulations, ensuring organized and sustainable territorial governance. Within administrative law, these regulations are key in managing land use to address social, economic, and environmental demands. This article aims to explore the role of local governments in spatial planning and building regulations through the lens of administrative law. The focus is on evaluating the responsibilities and powers of local authorities in policy formulation, alongside the challenges encountered in implementing spatial planning and building policies at the local level.